A Systematic Review of Severe Neurological Manifestations in Pediatric Patients with Coexisting SARS-CoV-2 Infection - Lauren O'Loughlin; Nilo Alvarez Toledo; Leon Budrie; Randall Waechter; Joanna Rayner (MDPI AG, 2021)
SARS-CoV-2 infection in children produces mild respiratory symptoms or no symptoms at all in most cases. Some pediatric patients develop a severe complication associated with high mortality, the multisystem inflammatory syndrome in children (MIS-C). In both scenarios, there are reports of neurological manifestations. This article aims to review the cases of pediatric patients with severe neurological issues and a coexisting positive SARS-CoV-2 test. A literature search was performed between March 2020 and May 2021. The results included the data from 41 studies, with 159 children with severe neurological manifestations, within an age range from 24 h to 17 years. The neurological disorders included 38 cases with stroke, 32 with encephalitis, 22 with encephalopathy, and 10 with Guillain-Barre syndrome. Sixty-five out of 159 cases with severe neurological manifestations were diagnosed with MIS-C. Direct neuroinvasion and the exaggerated immune response in some patients seem to be the most critical factors triggering these manifestations. Further research in the ongoing pandemic is needed to elucidate the precise mechanism.